Concept and practices of human capital development in Pakistan: A conceptual approach - Jabeen, Rubina (2017)
The concepts and practice of Human Capital Development have become prominent in modern management literature especially in this new millennium for one obvious reason: that is because Human Capital Development is one of the most important issues in the developing countries like Pakistan. Human Capital Development plays an important role in overall progress and productivity of an individual, organization and for the country.However, The practice of Human capital development in Pakistan is characterized by the absence of corporate cultures, weak enforcement of rules and regulations, poor financial management, operational inefficiencies, over staffing, unskilled employees, growing employee dissatisfaction, increasing quality complaints, government interference, and lack of work motivation results in low productivity. This phenomenon has, in turn, become a matter of concern to academics and professionals alike on the field. Consequently, the main objective of this paper is to present an overview of Human Capital Development with particular emphasis on its concepts and practice.A review of the relevant literature was conducted on Human Capital Development and its dimensions (Management supervision and guidance; competency and moral value) for adopted. Hence, this study provides a review of previous studies on the Human Capital Development light to expose on the potential benefits of the concept and its dimensions, HCD emphasized more on the competency development of human capital,i.e., knowledge and skills. Therefore greater attention has to be focused on developing not just the competency of human capital but also on their moral/ethical values.The Human Capital Development should be based on a holistic development change and comprehensive toward surviving in the economic downturn of the country.